KDM3A/Ets1 epigenetic axis contributes to PAX3/FOXO1‐driven and independent disease‐promoting gene expression in fusion‐positive Rhabdomyosarcoma. Issue 10 (5th August 2020) - Sobral, Lays M.; Hicks, Hannah M.; Parrish, Janet K.; McCann, Tyler S.; Hsieh, Joseph; Goodspeed, Andrew; Costello, James C.; Black, Joshua C.; Jedlicka, Paul
Abstract : Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma in children and young adults. RMS exists as two major disease subtypes, oncofusion‐negative RMS (FN‐RMS) and oncofusion‐positive RMS (FP‐RMS). FP‐RMS is characterized by recurrent PAX3/7‐FOXO1 driver oncofusions and is a biologically and clinically aggressive disease. Recent studies have revealed FP‐RMS to have a strong epigenetic basis. Epigenetic mechanisms represent potential new therapeutic vulnerabilities in FP‐RMS, but their complex details remain to be defined. We previously identified a new disease‐promoting epigenetic axis in RMS, involving the chromatin factor KDM3A and the Ets1 transcription factor. In the present study, we define the KDM3A and Ets1 FP‐RMS transcriptomes and show that these interface with the recently characterized PAX3/FOXO1‐driven gene expression program. KDM3A and Ets1 positively control numerous known and candidate novel PAX3/FOXO1‐induced RMS‐promoting genes, including subsets under control of PAX3/FOXO1‐associated superenhancers (SE), such as MEST. Interestingly, KDM3A and Ets1 also positively control a number of known and candidate novel FP‐RMS‐promoting, but not PAX3/FOXO1‐dependent, genes. Epistatically, Ets1 is downstream of, and exerts disease‐promoting effects similar to, both KDM3A and PAX3/FOXO1. MEST also manifests disease‐promoting properties in FP‐RMS, and KDM3A and Ets1 each impacts activation of the PAX3/FOXO1‐associated MEST SE. Taken together, our studies show that the KDM3A/Ets1 epigenetic axis plays an important role in disease promotion in FP‐RMS, and provide insight into potential new ways to target aggressive phenotypes in this disease. Abstract : Fusion‐positive rhabdomyosarcoma (FP‐RMS) is an aggressive pediatric cancer. The chromatin factor KDM3A and the downstream transcription factor Ets1 comprise a new epigenetic axis that works together with, as well as independently of, the driver PAX3/FOXO1 oncofusion to upregulate disease‐promoting gene expression and phenotypic properties in FP‐RMS. These findings offer new insights into potential ways to target aggressive properties in this disease.